Dracula : son of the dragon - Sable, Mark (Dark Horse Books, a division of Dark Horse Comics LLC, 2021)
"A blood-soaked epic of the real-life Vlad the Impaler's transformation into the vampire Dracula. Part historical fiction, part horror fantasy, this graphic novel is brought to you by writer Mark Sable (The Dark, Graveyard of Empires, Unthinkable) and artist Salgood Sam (Dream Life, Therefore Repent, Sea of Red)"--